The participation of women from rural areas in development projects for sustainable livelihoods: a case of community groups in Maqongqo Area, KwaZulu-Natal Province - Mazibuko, Eugene Futhi Again (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.